Is imagining a voice like listening to it? Evidence from ERPs - Zhou, Peiyun; Garnsey, Susan; Christianson, Kiel (Cognition, 2019)
•Imaging a speaker’s voice during silent reading is similar to listening to speech.•Imagining a native speaker’s voice when reading silently elicits similar ERP effects as normal silent reading.•Imagining a non-native speaker’s voice reduces N400 and P600 when processing ungrammatical sentences.•Readers appear to “forgive” grammatical errors when imagining the voice of a non-native speaker. Readers who have seen the Harry Potter movies before reading the novels may “hear” actors' voices in their heads when they later read the books. This phenomenon of mentally simulating the voice of speakers depicted in texts has been referred to as auditory perceptual simulation (APS). How much is this mental simulation of voices like listening to actual voices? Two event-related potential (ERP) experiments examined the auditory perceptual simulation of native and non-native English speech while participants silently read English sentences containing subject-verb agreement errors or pronoun-case errors. The aim was to compare readers’ ERPs when imagining native and non-native speech to the results of Hanulíková, van Alphen, van Goch, and Weber (2012), who recorded ERPs while participants listened to native and non-native speech and found that native-speaking listeners “forgive” errors (signaled by reduced P600 effects) by non-native speakers. Our participants listened to samples of a native and a non-native English speaker's speech and were then asked to imagine the voice of either one or the other speaker while reading sentences. Results revealed differences in N400 and P600 waveforms when imagining the non-native speaker's voice compared to the native speaker's voice. Importantly, when imagining the non-native speaker committing subject-verb agreement errors, P600 amplitudes were no different from error-free items.